2010
DOI: 10.1037/a0020149
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of bullying and victimization in childhood and adolescence: A meta-analytic investigation.

Abstract: Research on the predictors of 3 bully status groups (bullies, victims, and bully victims) for school-age children and adolescents was synthesized using meta-analytic procedures. The primary purpose was to determine the relative strength of individual and contextual predictors to identify targets for prevention and intervention. Age and how bullying was measured were also considered as moderators. From an original pool of 1,622 studies conducted since 1970 (when research on bullying increased significantly), 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

96
1,110
19
110

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,404 publications
(1,335 citation statements)
references
References 90 publications
96
1,110
19
110
Order By: Relevance
“…These results confirm the empirical results of previous studies, which reported the same trend (Cook et al, 2010;Marsh, Nagengast, Morin, Parada, Craven, & Hamilton, 2011;Olweus, 1993;Polak, Smrtnik Vitulić, & Vošnjak, 2011). The most common explanation of such results refers to different patterns of socialization in boys and girls.…”
Section: Differences Between Groups Of Victims and Bullies Regardingsupporting
confidence: 82%
See 2 more Smart Citations
“…These results confirm the empirical results of previous studies, which reported the same trend (Cook et al, 2010;Marsh, Nagengast, Morin, Parada, Craven, & Hamilton, 2011;Olweus, 1993;Polak, Smrtnik Vitulić, & Vošnjak, 2011). The most common explanation of such results refers to different patterns of socialization in boys and girls.…”
Section: Differences Between Groups Of Victims and Bullies Regardingsupporting
confidence: 82%
“…At the same time, the fact that research shows that peer influence is the strongest predictor for PB (Cook et al, 2010) should be considered. Namely, the non-involved students play an important part in PB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Children who are exposed to bullying are more likely than others to have low social skills, to suffer from internalizing and externalizing problems, and to have a low self-concept (Card & Hodges, 2008;Cook, Williams, Guerra, Kim, & Sadek, 2010). The causal links, however, are not always clear as, for instance, poor social skills and internalizing problems may be the causes as well as consequences of being bullied.…”
Section: Individual-level Characteristics Associated With Exposure Tomentioning
confidence: 93%
“…The term "bully-victim" has been widely used in the extant research (Cook et al 2010), perhaps implying that some children alternate between the roles of aggressor and victim. Other formulations have emphasized difficulties in selfregulation that might include impulsiveness, poorly modulated affect, and over reactivity (Schwartz et al 2001).…”
mentioning
confidence: 99%